A realidade como princípio metodológico no ensino da matemática - SILVA, Luiza Pereira da (2004)
This study has the purpose to argue the actions developed in the school in an interdisciplinary conception, having the Generating Subject as axle of curricular orientation, using as a methodological strategy for construction of the thematic nets in the classroom the work projects (inquiry projects). We believe that the process of teach-learning and the construction of the school and scientific knowledge from the valuation and approach with knowledge of the reality (daily knowledge), will become more efficient in a dialogical process between students, teachers and knowledge that interact in a movement of orientation on the part of the teacher and for the search to understanding methematics knowledge, applying it and systemizing it toward new knowledge.